An exploration of symptom burden and its management, in Saudi Arabian patients receiving haemodialysis, and their caregivers: a mixed methods study protocol - Alshammari, Bushra (BMC Nephrol, 2019)
BACKGROUND: Globally 10% of the population worldwide are affected by chronic kidney disease (CKD), making it one of the most prevalent chronic diseases. Several studies have highlighted that the symptoms of CKD have a significant impact on patients. A number of symptoms, including fatigue and depression, are associated with poor patient health, increased risk of hospitalisation and mortality. Physical and emotional symptoms often remain under-recognised and largely untreated; however, patients often create a variety of self-management strategies to meet the challenges of these symptoms. There is a lack of knowledge regarding symptom burden and the experiences of patients receiving haemodialysis (HD) and their caregivers, particularly in Saudi Arabia, therefore, this study aims to explore symptom burden and its management amongst patients receiving HD in addition to caregiver burden. METHOD: A mixed methods, sequential, explanatory design consisting of two phases: phase 1 involves a cross-sectional study design with a planned convenience sample size of 141 patients who will be recruited from King Khaled hospital, Saudi Arabia. Thirty-two physical and psychological symptoms will be measured using the Chronic Kidney Disease-Symptom Burden Index (CKD-SBI). Additionally, 130 caregivers will complete the Arabic version of the Zarit Burden Interview (ZBI-22) to identify the level of burden in the caregivers of patients on maintenance HD. Phase 2 of the study is a qualitative descriptive design involving semi-structural interviews with 15 eligible patients currently receiving HD. The selection of participants for interviews will be based on the patients’ total CKD-SBI scores with five individuals recruited from the lowest, median and highest percentiles. Additionally, 15 caregivers of the patients to be interviewed, will also be recruited and interviewed. DISCUSSION: This study focuses on a wide number of physical and psychological symptoms experienced by patients receiving HD. It will also focus on the effective management strategies patients employ to help reduce their perceived symptoms. Burden in caregivers of patients receiving HD will also be explored. Furthermore, the association between symptom burden and caregiver burden will be investigated. Findings from this study will provide evidence to help health care providers to develop effective interventions to assess and manage symptoms in patients receiving HD.